Involvement of Hormone- and ROS-Signaling Pathways in the Beneficial Action of Humic Substances on Plants Growing under Normal and Stressing Conditions - Andrés Calderín García (BioMed Research International, 2016)
The importance of soil humus in soil fertility has been well established many years ago. However, the knowledge about the whole mechanisms by which humic molecules in the rhizosphere improve plant growth remains partial and rather fragmentary. In this review we discuss the relationships between two main signaling pathway families that are affected by humic substances within the plant: one directly related to hormonal action and the other related to reactive oxygen species (ROS). In this sense, our aims are to try the integration of all these events in a more comprehensive model and underline some points in the model that remain unclear and deserve further research.